Delayed Thermal Relaxation of Rapid Cooling Neutron Stars: Nucleon Superfluidity and Nonnucleon Particles - Zhonghao Tu; Ang Li (The Astrophysical Journal)
The thermal relaxation time of neutron stars, typically defined by a sudden drop in surface temperature, is usually on the order of 10–100 yr. In this study, we investigate neutron star thermal relaxation by incorporating nucleon superfluidity and nonnucleonic particles, specifically considering hyperons as a representative case. We find that rapidly cooling neutron stars driven by neutron superfluidity and direct Urca processes demonstrate delayed thermal relaxation under specific physical conditions. The former requires that the neutron ^3 P _2 critical temperature is small enough, whereas the latter depends on the presence of a small core that permits direct Urca processes. To explore these scenarios, we propose simple theoretical frameworks to describe these delayed thermal relaxation behaviors and discuss how a recently established enhanced modified Urca rate influences the relaxation time. By confronting the theoretical results with the observation of Cassiopeia A, we can effectively constrain the maximum neutron ^3 P _2 critical temperature.